2022
DOI: 10.1177/00223433221092815
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Online Political Influence Efforts dataset

Abstract: This article introduces a dataset on the covert use of social media to influence politics by promoting propaganda, advocating controversial viewpoints, and spreading disinformation. Influence efforts (IEs) are defined as: (i) coordinated campaigns by a state, or the ruling party in an autocracy, to impact one or more specific aspects of politics at home or in another state, (ii) through media channels, including social media, by (iii) producing content designed to appear indigenous to the target state. Our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…11 The manipulation of information can also be used by foreign powers to interfere in democratic regimes. Martin et al (2018) draw on more than 460 media reports to identify 53 foreign influence efforts, targeting 24 different countries between 2013 and 2018. They show that 72% of these foreign influence campaigns were conducted by Russia, with China, Iran, and Saudi Arabia accounting for most of the remainder.…”
Section: Manipulation Of Informationmentioning
confidence: 99%
“…11 The manipulation of information can also be used by foreign powers to interfere in democratic regimes. Martin et al (2018) draw on more than 460 media reports to identify 53 foreign influence efforts, targeting 24 different countries between 2013 and 2018. They show that 72% of these foreign influence campaigns were conducted by Russia, with China, Iran, and Saudi Arabia accounting for most of the remainder.…”
Section: Manipulation Of Informationmentioning
confidence: 99%
“…Academics, journalists, online platforms, and governments have demonstrated that online covert propaganda campaigns are frequent and ongoing (1,2). Disclosures of Russian disinformation campaigns on social media targeting the U.S. in 2016 heightened awareness of these efforts and caused platforms to commit more resources to finding and suspending these operations (3).…”
Section: Main Text: Introductionmentioning
confidence: 99%
“…Yet others have focused on "hybrid" or autocratizing political contexts that illustrate the process of protest dynamics and the spread of tolerance or intolerance (Lynch 2011;Siegel and Badaan 2020;Siegel et al 2021;Steinert-Threlkeld 2017). A new area of work is the study of foreign influence operations in which outside actors attempt to manipulate social media discourse within the domestic politics of other countries (Alizadeh et al 2020;Courchesne 2021;Martin, Shapiro, and Nedashkovskaya 2019). Violence due to online mobilization is another vibrant area of research, with a focus on how armed groups try to attract recruits and possible government countermeasures (Mitts 2019;Mitts, Phillips, and Walter 2022;Müller and Schwarz 2021).…”
Section: Conceptualizing Coalitions Onlinementioning
confidence: 99%
“…The top-left quadrant in Table 1 captures research on the relationship between elite messaging and public rhetoric on social media. It includes, for example, research on how foreign regimes may try to spread disinformation (Aral and Eckles 2019; Martin, Shapiro, and Nedashkovskaya 2019) or how insurgent groups disseminate propaganda to attract potential supporters (Mitts, Phillips, and Walter 2022). The top-right quadrant reflects work examining the multidirectional interaction between elites and citizens; it includes the large body of research on the interaction of politicians’ constituents on social media (Barberá et al 2019; Barberá and Zeitzoff 2018; Silva and Proksch 2021) and online mobilization efforts, such as those used in mass protest (Larson et al 2019; Steinert-Threlkeld 2017).…”
Section: Conceptualizing Coalitions Onlinementioning
confidence: 99%